URGENSI DAN KONSEP IDEAL SERTIFIKASI HAKIM LINGKUNGAN HIDUP BAGI PERWUJUDAN EFEKTIVITAS PENEGAKAN HUKUM LINGKUNGAN INDONESIA - indah nur shanty saleh (Universitas Katolik Indonesia Atma Jaya, 2021)
Abstract The judiciary body is at the forefront of enforcing Indonesian environmental law through judges' decisions that prioritize the preservation of environmental functions. Judges who have competence in the field of environmental law are expected to be able to make decisions in favor of environmental justice. However, the reality is that there are still many judges' decisions on environmental cases that are not in favor of justice and the interests of the preservation of environmental functions. The existence of Supreme Court Decree Number 134 / KMA / SK / IX / 2011 concerning Certification of Environmental Judges is also considered not optimal in increasing the competence of judges regarding environmental cases decision. This study is to identify, analyze, and explain the implications of environmental judge certification for the effectiveness of Indonesian environmental law enforcement. The type of research used is juridical normative or doctrinal, using secondary data sources which include primary, secondary and tertiary legal materials. This research concludes that environmental judge certification is literally becoming an important and strategic aspect in the effort to bring the effectiveness of environmental law enforcement in Indonesia into reality. Up to now, the regulation of environmental judge certification has not been fully optimally implemented. This research considers that it is important to carry out legal reconstruction, in order to obtain an ideal concept related to environmental judge certification in an effort to have a solid and effective Indonesian environmental law enforcement. Keywords: judge certification, environment, law enforcement.